ANALISIS KEBIJAKAN PEMBUATAN AKTA KELAHIRAN DI KOTA SEMARANG - Achmad Faizun M; Tri Yuniningsih; Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Birth certificate on when these undergo elimineted dispensation, policy problem among them procedures to be to other institutions, the cost is very expensive, there are still scalpers, and the system arsiping fucked-up. The central government want of all citizens must indonesia recorded events its birth, because a function of birth certificate some of them are very important for the citizens, to document the state and evidence autentik incident to birth. See the problems very much is good news in the analysis of a policy of making birth certificate.The purpose of this research was to find the best alternatives from these problems and for the creation of a birth certificate procedures become better in order to increase production of a birth certificate to be on the rise. To answer these goals using the theory of policy analysis Brigmen and Davis refers to the stages of policy analysis with design research discription.Research showed want birth certificate become more dispensations and socialization. Coordination between each employee must also done so that the policy walk should be.